Important Role of Additive in Morphology of Stretchable Electrode for Highly Intrinsically Stable Organic Photovoltaics - Shin, Eul-Yong; Park, So Hyun; Jeon, Yeonjee; Kim, Kyuyeon; Lee, Giseok; Lee, Jung-Yong; Son, Hae Jung (AMER CHEMICAL SOC, 2023)
Developing intrinsically stretchable organic photovoltaics(IS-OPVs)is crucial for serving as power sources in future portable and wearableelectronics. PEDOT:PSS is most commonly used to prepare highly conductive,transparent electrodes with high stretchability. The mechanical propertiesof PEDOT:PSS films are significantly affected by their morphology,which is primarily determined by the processing additives used. Weinvestigate the effects of two additives, poly(ethylene glycol) (PEG)and (3-glycidyloxypropyl)-trimethoxysilane (GOPS), on the stretchabilityof the electrode. The PEG additive forms hydrogen bonds with sulfonylgroups of PSS without significant interaction among itself, whichreleases mechanical stress in the PSS-rich region of the PEDOT:PSSfilms. On the other hand, the GOPS additive not only forms hydrogenbonds with PSS but also undergoes a chemical reaction to create across-linked structure within the film, which effectively enhancesthe stretchable properties of the PEDOT:PSS film. In addition, theGOPS promotes a more hydrophilic surface compared to PEG, resultingin improved adhesion to the upper layer in IS-OPV devices. This improvesthe stretchability of IS-OPV devices, as well as their solar cellperformance. We demonstrate IS-OPVs that are prepared using GOPS bya non-spin-coating method and these devices exhibit higher performancecompared with PEG-based counterparts. Furthermore, the GOPS basedIS-OPV shows significantly improved mechanical stability, enablingit to retain 90% of its initial efficiency when subjected to 20%strain.